1997
DOI: 10.1046/j.1365-2796.1997.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function, vascular risk factors and education. A cross‐sectional study based on a cohort of 70‐year‐old men

Abstract: Objectives.A low level of education is associated with an increased risk of developing a dementia disorder, as well as with a higher risk of cardiovascular disease. The aim of this study was to investigate the association between education and cardiovascular risk factors, and to study the relation between these factors and cognitive function in elderly men. Design. Cross-sectional population-based study. Setting. Uppsala, Sweden. Subjects. 504 men aged 69-74 years, participants in a longitudinal health survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
51
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 39 publications
11
51
0
Order By: Relevance
“…Moreover, there is evidence that male gender potentiates both cerebraldegenerative and cognitive changes related to hypertension in older adult subjects. 22 Our findings with respect to obesity are consistent with the two studies that have reported adverse effects of obesity on cognitive functioning in males, 11,12 but neither study included women in the samples. Sex differences in sample size do not explain our finding.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, there is evidence that male gender potentiates both cerebraldegenerative and cognitive changes related to hypertension in older adult subjects. 22 Our findings with respect to obesity are consistent with the two studies that have reported adverse effects of obesity on cognitive functioning in males, 11,12 but neither study included women in the samples. Sex differences in sample size do not explain our finding.…”
Section: Discussionsupporting
confidence: 89%
“…Only two studies have provided some evidence that obesity per se is associated with lowered cognitive functioning in men. 11,12 However, these studies failed to address whether obesity was associated with cognitive performance independently of the effects of diabetes, hypertension, cholesterol levels, and cigarette smoking. Moreover, they did not include controls for cardiovascular diseases and events that may have been correlated with overweight or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Two other populationbased studies have noted lower levels of cognitive function in the presence of obesity. 6,7 However, these studies were limited by the presence of major confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Obesity has been associated with poorer cognitive function in several population-based investigations. [6][7][8] However, two of these studies did not control for major confounding variables such as other cardiovascular risk factors and cardiovascular or metabolic diseases. 6,7 Examining participants from the Framingham Study who were free of stroke, dementia, or diagnosed cardiovascular disease, Elias et al 8 reported that obese men performed significantly more poorly than nonobese men across several tests of memory and executive function after controlling for multiple confounding variables.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension in midlife is a well-established risk factor for dementia [4,5] that has also been connected to cognitive decline [6,7]. Dyslipidaemia [7], insulin resistance, type 2 diabetes [8,9,10] and obesity [11,12] have also been identified as risk factors in this context.…”
Section: Introductionmentioning
confidence: 99%